Hybrid Porphyrin-Polymeric Materials and their Amazing Applications: A Review - Fagadar-Cosma, Gheorghe; Birdeanu, Mihaela; Fagadar-Cosma, Eugenia (Journal of Research Updates in Polymer Science, 2016)
Porphyrins are versatile multifunctional biomimetic molecules that are obtained by condensation of pyrrole with the desired aromatic aldehydes. The porphyrin structure can be synthetically modified by either introduction of various peripheral functional groups or metals in its core, allowing creation of various porphyrin derivatives that exhibit amazing optoelectronic properties. This feature makes porphyrins molecules extremely useful especially in hybrid combination with photonic, electronic and magnetic compounds. This review is focused on the more recently obtained porphyrin-polymeric materials and on their various analytical, industrial and medical applications. The study underlines the assembling capacity of these porphyrin-polymer hybrids to form supramolecular tunable architectures by means of the association of more building block units. Porphyrin-polymer nano- and micro-materials play a preeminent role in sensing applications involving chromophores in the formulation of organic solar cells - due to their capacity to generate photo induced charge separation centers - and as new materials with interesting catalytic properties. Besides these technical applications, the photobactericidal activity of these porphyrin–polymer materials was evaluated against Gram positive and Gram negative strains bacteria and they represent an alternative to antibiotics in order to overcome the growing bacterial multiresistance. Polymer functionalization with porphyrin is commonly used to overcome some drawbacks such as self-quenching and photo-toxicity to the skin produced by the bare porphyrins, when used as photosensitizers in the non-invasive Photodynamic therapy of cancer (PDT).